Endogenous zebrafish proneural Cre drivers generated by CRISPR/Cas9 short homology directed targeted integration - Maira P. Almeida (Nature Portfolio, 2021)
Abstract We previously reported efficient precision targeted integration of reporter DNA in zebrafish and human cells using CRISPR/Cas9 and short regions of homology. Here, we apply this strategy to isolate zebrafish Cre recombinase drivers whose spatial and temporal restricted expression mimics endogenous genes. A 2A-Cre recombinase transgene with 48 bp homology arms was targeted into proneural genes ascl1b, olig2 and neurod1. We observed high rates of germline transmission ranging from 10 to 100% (2/20 olig2; 1/5 neurod1; 3/3 ascl1b). The transgenic lines Tg(ascl1b-2A-Cre) is75 , Tg(olig2-2A-Cre) is76 , and Tg(neurod1-2A-Cre) is77 expressed functional Cre recombinase in the expected proneural cell populations. Somatic targeting of 2A-CreERT2 into neurod1 resulted in tamoxifen responsive recombination in the nervous system. The results demonstrate Cre recombinase expression is driven by the native promoter and regulatory elements of the targeted genes. This approach provides a straightforward, efficient, and cost-effective method to generate cell type specific zebrafish Cre and CreERT2 drivers, overcoming challenges associated with promoter-BAC and transposon mediated transgenics.